2005
DOI: 10.1093/pcp/pci045
|View full text |Cite
|
Sign up to set email alerts
|

Some Cyanobacteria Synthesize Semi-amylopectin Type α-Polyglucans Instead of Glycogen

Abstract: It is widely accepted that green plants evolved the capacity to synthesize the highly organized branched alpha-polyglucan amylopectin with tandem-cluster structure, whereas animals and bacteria continued to produce random branched glycogen. Although most previous studies documented that cyanobacteria accumulate glycogen, the present study shows explicitly that some cyanobacteria such as Cyanobacterium sp. MBIC10216, Myxosarcina burmensis and Synechococcus sp. BG043511 had distinct alpha-polyglucans, which were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 18 publications
3
61
0
1
Order By: Relevance
“…It has not been detected in cyanobacteria. This is true also for those cyanobacteria that synthesize starch (semiamylopectin) and could therefore be considered ancestors of chloroplasts (150). The evolutionary origin of the [FeFe] hydrogenase of green algae is a mystery yet to be resolved (132,146).…”
Section: Hydrogenases In Generalmentioning
confidence: 99%
“…It has not been detected in cyanobacteria. This is true also for those cyanobacteria that synthesize starch (semiamylopectin) and could therefore be considered ancestors of chloroplasts (150). The evolutionary origin of the [FeFe] hydrogenase of green algae is a mystery yet to be resolved (132,146).…”
Section: Hydrogenases In Generalmentioning
confidence: 99%
“…Until recently, the distribution of starch seemed restricted to photosynthetic eukaryotes, including several secondary endosymbiosis lineages derived from Archaeplastida, such as the cryptophytes (Deschamps et al, 2006), the dinoflagellates (Dauvillée et al, 2009), and some apicomplexa parasites (Coppin et al, 2005). However, more recent studies revealed the existence of starch-like structures in unicellular diazotrophic cyanobacteria belonging to the order Chroococcales (Nakamura et al, 2005;Deschamps et al, 2008;Suzuki et al, 2013). The presence of anomalous glycogen particles had already been identified previously in this clade, while it is only very recently that this material was recognized as starch-like and the term "semiamylopectin" was coined to describe the major amylopectin-like fraction within these granules (Schneegurt et al, 1994;Suzuki et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A second observation inspiring the hypothesis of Deschamps et al [54] is the discovery of starch-like structures in unicellular group V diazotrophic cyanobacteria [55]. These starch-like molecules are synthesized using enzymes that are phylogenetically related to the ones involved in starch metabolism in Archaeplastida, and have not been found in any other group of Cyanobacteria so far.…”
Section: Metabolic Symbiosis and Primary Endosymbiosismentioning
confidence: 95%